2014
DOI: 10.1371/journal.pcbi.1003693
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Prediction and Validation of Peptides That Bind Human Prosurvival Bcl-2 Proteins

Abstract: Programmed cell death is regulated by interactions between pro-apoptotic and prosurvival members of the Bcl-2 family. Pro-apoptotic family members contain a weakly conserved BH3 motif that can adopt an alpha-helical structure and bind to a groove on prosurvival partners Bcl-xL, Bcl-w, Bcl-2, Mcl-1 and Bfl-1. Peptides corresponding to roughly 13 reported BH3 motifs have been verified to bind in this manner. Due to their short lengths and low sequence conservation, BH3 motifs are not detected using standard sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 50 publications
1
56
0
Order By: Relevance
“…22,30,32 Recently, DeBartolo et al reported dissociation constants for the five human Bcl-2 homologs binding to 36 new, computationally identified candidate BH3 peptides from the human proteome. 46 In Fig. 3b, we compare the binding patterns of the three viral Bcl-2 homologs to those of the human homologs for these 36 BH3-like peptides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,30,32 Recently, DeBartolo et al reported dissociation constants for the five human Bcl-2 homologs binding to 36 new, computationally identified candidate BH3 peptides from the human proteome. 46 In Fig. 3b, we compare the binding patterns of the three viral Bcl-2 homologs to those of the human homologs for these 36 BH3-like peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we designed the libraries using mutational data from SPOT arrays and predictions made using STATIUM, a statistical potential that can evaluate mutations based on analysis of human or viral Bcl-2 crystal structures or homology models. 46,48 We also used Illumina sequencing data from a yeast surface display library of Bim BH3 variants previously screened for KSBcl-2 binding. 25 The computationally assisted library design process (described in further detail in the Materials and Methods) focused on including residues that were tolerated by the viral Bcl-2 proteins and that weakened binding to Mcl-1 and, for the BHRF1 library, Bfl-1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most notably, template-based methods are having considerable biological impact, and have been applied to identify, almost always with experimental validation, previously unknown protein-protein interactions [13*,40*], RNA-binding proteins [23*], membrane binding-proteins [48*], enzyme families [49*], drug targets [21*], to analyze biological pathways [50,51] and to understand the relationship between genetic variation and disease [52*]. Protein structure is, of course, a key component of these approaches.…”
Section: Resultsmentioning
confidence: 99%
“…identifying residues that occur more frequently in certain types of interfaces, as compared to a non-interfacial background. This approach has recently been used to identify novel proteins that interact with DNA or RNA [22,23*] and novel interactors of Bcl2 proteins [40*]. In another approach, a large set of protein-peptide structures was examined to construct, for each of the twenty amino acids, a three-dimensional grid of boxes containing the set of chemical groups that more frequently interact with that amino acid in protein-peptide interfaces [41].…”
Section: Template Familiesmentioning
confidence: 99%